DETEKSI DINI KADAR GLUKOSA DARAH SEWAKTU DAN TEKANAN DARAH DI MASYARAKAT DESA CARANG WULUNG KECAMATAN WONOSALAM KABUPATEN JOMBANG - Ifa Nofalia; Suhendra Agung Wibowo; Endang Yuswatiningsih; Dwi Prasetyaningati; Iva Milia Hani Rahmawati; Hindyah Ike Suhariati (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2024)
Insufficient knowledge and minimal public awareness of the importance of health checks are the main problems that must be addressed immediately. Diabetes mellitus and blood pressure are the two non-communicable diseases that most people suffer from. So the target of implementing the community service program is to provide education by means of health education and early detection of instantaneous blood glucose levels and blood pressure in the community with the aim of increasing community knowledge about disease and increasing awareness of the importance of early screening in the community of Carang Wulung Village, Wonosalam District. , Jombang Regency. The result was that almost half of the people who took blood sugar checks experienced hyperglycemia, 37 people (49.3%) and the majority of people who took blood pressure checks experienced hypertension, 44 people (58.7%). Regarding knowledge before health education was carried out, the majority of people still had insufficient knowledge about diabetes mellitus and hypertension with a total of 52 people (69.3%). After health education was carried out, almost all people had good knowledge about diabetes mellitus and hypertension with a total of 69 people (92%). In conclusion, the service activities that have been carried out run smoothly and receive support from all parties, so it is hoped that the public will better understand the importance of early prevention so that more serious health problems do not occur